Advances and Challenges of Using Experimental Pigs in Da Vinci Surgical Robot Training - LIU Yishu; CAI Liping (Shiyan dongwu yu bijiao yixue)
Experimental pigs occupy a crucial position in life sciences research and have been indispensable in advancing the practical application of new clinical technologies and methods. The Da Vinci Surgical Robot System, developed by Intuitive Surgical in the United States, has been widely used across various surgical fields since its approval by the U.S. Food and Drug Administration (FDA) in 2000, and is highly esteemed for its precision and accuracy. With the continuous advancement of surgical robot technology, the skill requirements for medical professionals have also increased. Consequently, surgical skills training has become an essential component of ensuring both surgical safety and effectiveness. This article briefly reviews the current status of Da Vinci surgical robot training, both domestically and internationally, with a focus on the practical application of experimental pigs in domestic Da Vinci surgical robot training. It emphasizes that experimental pigs not only effectively simulate the human surgical environment, enabling trainees to practice in a safe and controlled setting, but also help accelerate the trainees' familiarity with and mastery of the surgical robot. This, in turn, significantly shortens the learning curve, enhances the precision and stability of surgical procedures, and reduces surgical risks. However, the use of experimental animals in surgical robot training also encounters challenges, including limitations caused by the differences between experimental animals and humans, potential ethical concerns, and public opinion pressures. In response to these challenges, the paper proposes suggestions such as improving and enforcing ethical regulations, as well as advancing the development of virtual reality (VR) and augmented reality (AR) technologies. These efforts aim to reduce reliance on experimental animals in surgical training while enhancing training effectiveness, thereby contributing to the innovation and development of Da Vinci surgical robot training models.